The Gaussian-Drude Lens: A Dusty Plasma Model Applicable to Observations Across the Electromagnetic Spectrum - Adam Rogers (Universe)
When radiation from a background source passes through a cloud of cold plasma, diverging lensing occurs if the source and observer are well-aligned. Unlike gravitational lensing, plasma lensing is dispersive, increasing in strength with wavelength. The Drude model is a generalization of cold plasma, including absorbing dielectric dust described by a complex index of refraction. The Drude lens is only dispersive for wavelengths shorter than the dust characteristic scale (<semantics>λ≪λd</semantics>). At sufficient photon energy, the dust particles act like refractive clouds. For longer wavelengths <semantics>λ≫λd</semantics>, the optical properties of the Drude lens are constant, unique behavior compared to the predictions of the cold plasma lens. Thus, cold plasma lenses can be distinguished from Drude lenses using multi-band observations. The Drude medium extends the applicability of all previous tools, from gravitational and plasma lensing, to describe scattering phenomena in the X-ray regime.